Trends of needle stick injuries among health care workers in a tertiary care center in South India - Suchitra Shenoy M; Harika Vangara; Joyce Emilda Rego; Irene Saldanha; Gracy Lobo; Shafir Kassim; Shrikala Baliga; Pavan M. R; Pooja Rao (Clinical Epidemiology and Global Health)
Objectives: Occupation blood exposures can happen in any health care facility. This usually happens due to needle or sharp injuries. The risk of transmission of blood borne pathogens is higher when the injury is due to hollow needle stick injuries. As a protocol the data regarding needle stick injuries in the hospital is captured. This study was taken to analyze the needle stick injuries over the past eleven years. Methods: A retrospective study was conducted from January 2012 to December 2022 to capture the needle stick injuries that took place in tertiary care hospital in Mangalore, Karnataka over the past 11 years. Data was entered and analyzed on Microsoft excel sheet 2021 (Redmond, Washington). Results: The trend showed that the incidence of needle stick injury was highest in the years 2013 and 2017. After the year 2013 the incidence drops slightly year after year due to the education and when retraining was reduced the incidence increased in 2017. The 11 years trend showed that doctors had the highest needle stick injury compared to nurses, housekeeping, and technician groups. Conclusion: The data suggests that the training can reduce the occurrence of needle stick injuries. The proper usage of personal protective equipment should be reinforced at all levels of the health care personnel.